The impact of macroeconomic variables on Kuala Lumpur industrial product / Allyssa Lai Danial Lai - Danial Lai, Allyssa Lai (2022)
This study examined the impact of macroeconomic variables on Kuala Lumpur Industrial Product in Malaysia. Due to Covid- 19, the performance of the Kuala Lumpur Industrial Product index has fluctuated. This issue leads to the study or the impact of macroeconomic variables on the Kuala Lurnpur Industrial Product index. There are tour macroeconomic variables such as exchange rates, money supply, inflation, and crude palm oil price. The data was collected Monthly and consisted of 73 observations from January 2016 until January 2022. Multiple regression tests the relationship between Kuala Lumpur Industrial Product and four macroeconomic variables. The results indicate that the stock market has significant relationship with money supply and crude palm oil price while the stock market showing insignificant relationship with exchange rate and inflation.